Raw material composition, thermosetting PAN-based interlayer film and its manufacturing method, and electrochemical device
By using a combination of PAN-based polymer material and a modification additive, the thermally cured intermediate layer is manufactured by melt extrusion tensile method, which solves the problems of safety and industrial production of liquid lithium-ion batteries and achieves high ionic conductivity and thermal stability.
Patent Information
- Application Number
- JP2024538729
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-27
- Filing Date
- 2022-12-26
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The prior art is difficult to effectively solve the safety problems of liquid lithium-ion batteries, especially under high energy density, and traditional polymer film formation technology cannot be suitable for the industrial production of PAN-based polymer electrolytes.
A heat-cured PAN-based intermediate layer is produced by melt extrusion stretching using a composition containing a PAN-based polymer material, a lithium salt and a modification additive. The modification additive is used to reduce the melting point of the polymer and form a three-dimensional interpenetrating structure to improve ionic conductivity.
The continuous industrial production of PAN-based intermediate layers with high ionic conductivity and thermal stability has been achieved, which solves safety and production problems, is environmentally friendly and reduces energy consumption.
Smart Images

Figure 2025503858000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a raw material composition, a thermosetting PAN-based interlayer and its manufacturing method, and an electrochemical device. Such interlayer includes a separator for a liquid electrochemical device and a solid electrolyte membrane for a solid electrochemical device, and belongs to the technical field of the design and manufacture of key materials for electrochemical energy storage devices. [Background technology]
[0002] At present, organic carbonate-based liquid electrolyte is generally used in large-scale commercialized lithium-ion batteries, which have safety problems such as leakage, combustion, and explosion. Moreover, as the battery energy density is constantly improving, its safety is constantly declining, which is a major factor that restricts the development of lithium-ion batteries; the thermal stability and mechanical strength of the intermediate separator used in liquid lithium-ion batteries play an extremely important role in the safety of the battery. On the one hand, when a separator with ion conductivity is used, the amount of electrolyte used can be greatly reduced, and the high heat resistance and high strength properties of the separator can be combined to comprehensively improve the safety of the liquid battery. On the other hand, in order to fundamentally solve the safety problems of batteries, a solid-state battery formed by using a solid electrolyte instead of the existing electrolyte and general separator has excellent safety, high energy density, and a wide operating temperature range, and is officially recognized as one of the most promising next-generation lithium-ion batteries for commercialization.
[0003] Up to now, various types of solid electrolyte materials such as sulfide electrolytes, oxide electrolytes, polymer electrolytes and halide electrolytes are included as solid electrolyte materials for solid batteries. Among them, polymer electrolytes are recognized as the type of solid electrolyte with the best processing performance and the fastest progress in industrial application, while PAN-based polymer electrolytes have been widely paid attention to and studied due to their high lithium ion conductivity. Among them, Chinese patent CN110165291A discloses a PAN-based composite electrolyte comparable to liquid electrolytes and its manufacturing method, and a large specific interfacial area is constructed by blown spinning and other techniques, and the ionic conductivity of the PAN-based polymer electrolyte is greatly improved by the surface lithium ion conduction method. However, the equipment required for the blown spinning technology requires high precision, resulting in low yield, poor consistency, and high difficulty in continuous production, which inhibits its industrialization development. Meanwhile, the thermal decomposition temperature of thermosetting PAN-based polymers is lower than their melting point temperature, so the traditional polymer film formation technology by melt extrusion drawing cannot be smoothly applied to the manufacturing method of such polymer electrolytes.
[0004] Therefore, providing a novel raw material composition for producing a thermosetting PAN-based interlayer film, a production method thereof, and its use have become problems that must be solved as soon as possible in this field. Summary of the Invention
[0005] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide a raw material composition for producing a thermosetting PAN-based interlayer film.
[0006] Another object of the present invention is to provide a manufacturing method for producing a thermosetting PAN-based interlayer film.
[0007] It is yet another object of the present invention to provide a thermosetting PAN-based interlayer film.
[0008] A final object of the present invention is to provide an electrochemical device.
[0009] In order to achieve the above object, one aspect of the present invention provides a raw material composition for producing a thermosetting PAN-based intermediate film, the raw material composition comprising a thermosetting PAN-based polymer material, a lithium salt, and a modifying aid, the mass ratio of the thermosetting PAN-based polymer material to the lithium salt being 20:1 to 3:1, the mass ratio of the thermosetting PAN-based polymer material to the modifying aid being 18:1 to 3:1, and the modifying aid comprising one or a combination of several selected from a carbonate-based modifying aid, a nitrile-based modifying aid, and an ionic liquid-based modifying aid.
[0010] As a specific embodiment of the raw material composition according to the present invention, the raw material composition further contains a ceramic material, and the amount of the ceramic material used is 5 to 80 wt % when the total weight of the thermosetting PAN-based polymer material is 100%.
[0011] In one specific embodiment of the raw material composition according to the present invention, the amount of the ceramic material used is 10 to 50 wt %.
[0012] In one specific embodiment of the raw material composition according to the present invention, the ceramic material contains an inorganic ion conductor and / or an inorganic non-ion conductor.
[0013] In one specific embodiment of the raw material composition according to the present invention, the inorganic ion conductor includes one or more selected from an oxide, a halide, a sulfide, a nitride, and a carbide, and the inorganic non-ion conductor includes one or more selected from a metal oxide and a non-metal oxide.
[0014] As a specific embodiment of the raw material composition according to the present invention, the ceramic material contains one or more oxides selected from a titanium-containing oxide, an aluminum-containing oxide, a boron-containing oxide, a zirconium-containing oxide, and a silicon-containing oxide.
[0015] In one specific embodiment of the raw material composition according to the present invention, the ceramic material includes one or a combination of several selected from silica, alumina, lithium titanium aluminum phosphate, lithium borate, lithium borate ester, lithium zirconate, garnet-type lithium lanthanum zirconium oxygen, lithium indium chlorohalide, arginine-type sulfide, lithium borohydride, and lithium lanthanum zirconium tantalum oxygen fast ion conductor. Here, the ceramic materials used in the present invention are all commercially available or can be produced by existing general methods.
[0016] In one specific embodiment of the above-described raw material composition according to the present invention, the modifying agent is a carbonate-based modifying agent or a nitrile-based modifying agent. By using the modifying agent when producing a thermosetting PAN-based intermediate film, the melting point of the thermosetting PAN-based polymer material can be lowered below the thermal decomposition temperature, and the thermosetting PAN-based polymer fiber can be obtained by melt drawing.
[0017] In one specific embodiment of the above-described raw material composition according to the present invention, the modifying aid is a carbonate-based modifying aid.
[0018] As a specific embodiment of the above-described raw material composition according to the present invention, the carbonate-based modifying aid includes one or more selected from ethylene carbonate, propylene carbonate, butene carbonate, and methyl ethyl carbonate.
[0019] As a specific embodiment of the raw material composition according to the present invention, the nitrile-based modifier auxiliary includes one or more selected from butyronitrile, succinonitrile, valeronitrile, hexanitrile, hexanedinitrile, heptanitrile, octanenitrile, n-dodecanitrile, n-tridecanonitrile, and n-tetradecanonitrile.
[0020] In one specific embodiment of the raw material composition according to the present invention, the cation in the ionic liquid-based modification aid comprises one or more selected from alkyl quaternary ammonium cations, alkyl quaternary phosphonium cations, N,N-dialkylimidazole cations, and N-alkylpyridine cations, and the anion comprises one or more selected from halogen ions, acetate ions, nitrate ions, tetrafluoroborate ions, and trifluoroacetate ions. In some embodiments of the present invention, the ionic liquid-based modification aid may be dimethyloctadecylhydroxyethylnitroammonium.
[0021] As a specific embodiment of the raw material composition according to the present invention, the lithium salt includes one or more selected from lithium hexafluorophosphate, lithium perchlorate, lithium bisoxalate borate, lithium difluoro(oxalato)borate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
[0022] As a specific embodiment of the above-described raw material composition according to the present invention, the thermosetting PAN-based polymer material is a copolymer of monomers including acrylonitrile or a derivative thereof, and itaconic acid or a derivative thereof.
[0023] As a specific embodiment of the raw material composition according to the present invention, the thermosetting PAN-based polymer material is a thermosetting PAN-based polymer fiber, and the number of the thermosetting PAN-based polymer fibers per unit membrane length is 1×10 3 ~1×10 7 / cm, the diameter of the thermosetting PAN-based polymer fiber is 50 nm to 2 μm, and the number of the thermosetting PAN-based polymer fibers per unit membrane length is calculated by the following formula 1), (Number 1) N=4ρ' / (dρ) Equation 1) In the above formula 1), ρ' is the intermediate compaction density of the thermosetting PAN-based polymer fiber, and is expressed in units of g / cm 3ρ is the density of the thermosetting PAN-based polymer fiber, and the unit is g / cm 3 and d is the average diameter of the thermosetting PAN-based polymer fibers, in cm.
[0024] In another aspect of the present invention, there is provided a method for producing a thermosetting PAN-based interlayer film, comprising premixing a raw material composition, melt extruding the raw material composition, and then performing a stretching process and / or a thin film forming process on the extruded prototype thick film to obtain the thermosetting PAN-based interlayer film, wherein the raw material composition is the raw material composition for producing the thermosetting PAN-based interlayer film described above.
[0025] In the present invention, the number of thermosetting PAN-based polymer fibers, the number of polymer interfaces, and the number of ceramic material and polymer interfaces (when a ceramic material is used) per unit membrane area can be increased by performing a stretching process on the extruded prototype thick film, and the obtained thermosetting PAN-based intermediate film has a three-dimensional interpenetrating structure in which the polymer interfaces and the ceramic material and polymer interfaces (when a ceramic material is used) are jointly formed by the aggregation of the thermosetting PAN-based polymer fibers and the random deposition / aggregation or dispersion of the ceramic material, thereby improving the ionic conductivity of the thermosetting PAN-based intermediate film and ensuring that the thermosetting PAN-based intermediate film finally reaches the required thickness.
[0026] In the thermosetting PAN-based interlayer film provided by the present invention, the ceramic material is randomly distributed in the form of aggregation / deposition or dispersion between the three-dimensional interpenetrating polymer phase, which can expand the amorphous region of the polymer, increase the number of interfaces of the solid electrolyte, and promote the dissociation of the lithium salt, etc.
[0027] In one specific embodiment of the manufacturing method for producing the above-described thermosetting PAN-based interlayer film according to the present invention, the temperature of the melt extrusion is 80 to 350°C, preferably 120 to 300°C.
[0028] In the solid electrolyte membrane, the lithium salt is partly dissolved in the polymer material and partly in an amorphous state (the lithium salt melts during processing and undergoes a certain bonding action with the thermosetting PAN-based polymer, resulting in an amorphous state rather than the original crystalline state), and a certain interaction occurs with the polymer material, causing the lithium salt to aggregate or adhere to the polymer surface. Compared to the total dissolution of the lithium salt during production by a solution method or the total concentration of the lithium salt during production by electrostatic spinning, the thermosetting PAN-based interlayer membrane provided by the present invention having such an existing form of the lithium salt has the highest ionic conductivity.
[0029] As a specific embodiment of the method for producing the above-described thermosetting PAN-based interlayer film according to the present invention, the method comprises the steps of: Step (1): Premixing a raw material composition for producing a thermosetting PAN-based interlayer film to obtain a premixed material; Step (2): melt extruding the premixed material to obtain a prototype thick film; Step (3): performing a stretching process and / or a thin film forming process on the prototype thick film to obtain the thermosetting PAN-based intermediate film; or Step (1)': A step of premixing a thermosetting PAN-based polymer material and a modifying auxiliary in a raw material composition for producing a thermosetting PAN-based intermediate film to obtain a premixed material; Step (2)': performing melt extrusion on the premixed material to obtain a prototype thick film; Step (3)': performing a stretching process and / or a thin film forming process on the prototype thick film to obtain an intermediate film product; Step (4)': immersing the intermediate film product in a lithium salt solution, or spraying the lithium salt solution evenly on both sides of the intermediate film product, and then drying the intermediate film product sprayed with the lithium salt solution or the intermediate film product obtained by immersion to remove the solvent, thereby obtaining the thermosetting PAN-based intermediate film; Includes.
[0030] As a specific embodiment of the above-described manufacturing method according to the present invention, in step (2) and step (2)', the apparatus used for melt extrusion independently includes one or a combination of several selected from a ball mill, an internal mixer, a single screw extruder, a twin screw extruder, a multi-screw extruder, and a granulator.
[0031] As a specific embodiment of the above-described manufacturing method according to the present invention, in step (2) and step (2)', the thickness of the prototype thick film is independently 100 μm to 2 mm.
[0032] As a specific embodiment of the above-described manufacturing method according to the present invention, in step (3) and step (3)', the stretching treatment independently includes transverse stretching, longitudinal stretching, or bidirectional stretching.
[0033] As a specific embodiment of the above-described production method according to the present invention, in step (4)', the drying temperature is 70 to 90°C.
[0034] As a specific embodiment of the above-described preparation method according to the present invention, in step (4)', the solvent used in the lithium salt solution is any one selected from common solvents, and preferably, the solvent is isopropanol and / or dimethyl ether.
[0035] In yet another aspect of the present invention, there is provided a thermosetting PAN-based interlayer film produced by the above-described production method.
[0036] As a specific embodiment of the thermosetting PAN-based intermediate film according to the present invention, the thermosetting PAN-based intermediate film is a liquid electrolyte separator or a solid electrolyte membrane, and the thickness of the solid electrolyte membrane is preferably 1 to 100 μm, more preferably 5 to 60 μm, and even more preferably 15 to 30 μm, and even more preferably, the range of the compaction density of the solid electrolyte membrane is 0.8 to 4.5 g / cm. 3 It is.
[0037] Finally, the present invention further provides an electrochemical device comprising a liquid electrochemical device and a solid electrochemical device, the liquid electrochemical device comprising a separator and the solid electrochemical device comprising a solid electrolyte membrane, the separator being the liquid electrolyte separator described above and the solid electrolyte membrane being the solid electrolyte membrane described above.
[0038] The liquid electrochemical device is not limited to a liquid ion battery (eg, liquid lithium ion battery, liquid sodium ion battery, liquid zinc ion battery, etc.), and the solid electrochemical device is not limited to a solid state battery.
[0039] Compared with existing technologies, the present invention can provide the following technical advantages: 1) The modifying aid used in the present invention is an aid that improves ion conductivity, reduces the polymer melting point, and improves film-forming processing performance. By adding the modifying aid to the raw material composition for producing a thermosetting PAN-based interlayer film and compounding it with a thermosetting PAN-based polymer material, the melting point temperature of the thermosetting PAN-based polymer material is reduced to be lower than the thermal decomposition temperature, ensuring that thermal decomposition does not occur during the melting process of the thermosetting PAN-based polymer material, and meeting the realization conditions of melt extrusion stretching technology. The thermosetting PAN-based interlayer film can be continuously produced by melt extrusion stretching technology. In addition, as a lithium ion conductive medium, the ion conductivity of the obtained interlayer film can be further improved (i.e., the thermosetting PAN-based interlayer film provided by the present invention is capable of ion conductivity), and the overall performance of the film can also be significantly improved. 2) Compared with the general jet spinning technology existing in this field, which can produce a solid electrolyte membrane with a large specific interfacial area, the melt extrusion drawing method used in the production method provided by the present invention is a simple and mature technology, has high efficiency, can be continuously mass-produced on a large scale, has high consistency, and can greatly improve the overall performance of the produced interlayer film while solving the problem of high difficulty in industrialization; and this production method does not use any solvents or related processes, is environmentally friendly, does not pollute the environment, and consumes low energy. [Brief description of the drawings]
[0040] In order to more clearly explain the embodiments of the present invention or the technical solutions of the existing technology, the drawings necessary for the description of the embodiments will be briefly described below. Needless to say, the drawings referred to in the following description are only related to some embodiments of the present invention, and those skilled in the art can obtain other drawings from these drawings without any creative work. [Figure 1] 1 is a real image of a thermosetting PAN-based composite solid electrolyte membrane provided in Example 1 of the present invention; [Diagram 2] FIG. 2 is a scanning electron microscope diagram of the thermosetting PAN-based composite solid electrolyte membrane provided in Example 1 of the present invention; [Figure 3a] FIG. 2 is a graph showing the ionic conductivity result of the thermosetting PAN-based composite solid electrolyte membrane provided in Example 1 of the present invention; [Figure 3b] FIG. 2 is a graph showing the ionic conductivity result of the thermosetting PAN-based composite solid electrolyte membrane provided in Example 2 of the present invention; [Figure 3c] FIG. 2 is a graph showing the ionic conductivity result of the thermosetting PAN-based composite solid electrolyte membrane provided in Example 3 of the present invention; [Figure 3d] FIG. 4 is a graph showing the ionic conductivity result of the thermosetting PAN-based composite solid electrolyte membrane provided in Example 4 of the present invention; [Figure 4] 1 is a charge / discharge cycle graph of a solid-state lithium ion battery provided in an application example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0041] The "ranges" disclosed in the present invention are given in the form of lower and upper limits. The lower and upper limits may each be one or more. A given range is defined by selecting one lower limit and one upper limit. The selected lower and upper limits define the boundaries of a particular range. All ranges defined in this manner are combinable, in other words, any lower limit can be combined with any upper limit to form a range. For example, if 60-120 and 80-110 are listed as ranges for a particular parameter, it is recognized that ranges of 60-110 and 80-120 are also contemplated. Also, if the minimum range value listed is 1, 2, and the maximum range value listed is 3, 4, and 5, then the ranges of 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all contemplated.
[0042] In the present invention, unless otherwise specified, the numerical range "a to b" represents a shorthand expression of any combination of real numbers between a and b, where a and b are both real numbers. For example ...
[0043] In the present invention, unless otherwise specified, all the embodiments and preferred embodiments mentioned in the present invention can be combined with each other to form a new technical solution.
[0044] In the present invention, unless otherwise specified, all technical features and preferred features mentioned in the present invention can be combined with each other to form a new technical solution.
[0045] In order to clarify the purpose, technical solution and advantages of the present invention, the present invention will be described in more detail below in conjunction with the drawings and examples. The examples described below are only a part of the examples of the present invention, not all of them, and are not intended to limit the scope of the present invention, but are merely for illustrating the present invention. Based on the examples of the present invention, all other examples that can be obtained by ordinary skilled artisans in the art without creative labor shall be included in the scope of protection of the present invention. In the examples, unless specific conditions are specified, the examples shall be carried out according to normal conditions or conditions provided by the manufacturer. For the reagents and equipment used, unless the manufacturer is specified, they shall be normal products available on the market.
[0046] Example 1 In this embodiment, a thermosetting PAN-based composite solid electrolyte membrane is provided which is produced by a production method including the following steps. (1) 50 g of polyacrylonitrile copolymer powder (Juma Manufacturing, PAN: 30,000 to 250,000), 10 g of lithium bis(trifluoromethanesulfonyl)imide, 3 g of vinyl carbonate, and 10 g of silica (D50 particle size: 210 nm) were premixed in a closed planetary mixer at a rotation speed of 1200 rpm for 10 min; (2) The premixed material is taken out and added into a single screw extruder for melt extrusion, the melt extrusion temperature is 195°C, and the thickness of the prototype thick film obtained by melt extrusion is 350 μm; (3) By performing bidirectional stretching and cooling on the prototype thick film, a 31 μm-thick formed solid electrolyte thin film, i.e., a thermosetting PAN-based composite solid electrolyte membrane, is obtained, as shown in Figure 1.
[0047] It is necessary to carry out the above steps (1) to (3) in a dry environment with a humidity of not more than 5%.
[0048] The compaction density of the thermosetting PAN-based composite solid electrolyte membrane produced in this example is 3.2 g / cm 3 , the density of thermosetting PAN-based polymer fiber is 1.184g / cm 3The diameter of the thermosetting PAN-based polymer fiber is 200 nm, and the number of thermosetting PAN-based polymer fibers per unit membrane area calculated by the above formula 1) is 5.4 × 10 5 The ionic conductivity of the thermosetting PAN-based composite solid electrolyte membrane is shown in FIG. 3a. The ionic conductivity calculated from the data shown in FIG. 3a is 5.4×10 -4 S / cm.
[0049] The scanning electron microscope image of the thermosetting PAN-based composite solid electrolyte membrane prepared in this embodiment is shown in Figure 2. As can be seen from Figure 2, the thermosetting PAN-based composite solid electrolyte membrane has stripe-shaped polymer fiber aggregates with a diameter of about 200 nm, while the ceramic particles are randomly deposited / aggregated or dispersed between the polymer fibers, so that the polymer fibers and the polymer fibers and the ceramic particles are alternately overlapped to jointly form a high-interface network with a three-dimensional interpenetrating structure, which can effectively improve the ionic conductivity of the thermosetting PAN-based composite solid electrolyte membrane.
[0050] In addition, in the thermosetting PAN-based composite solid electrolyte membrane provided by the present invention, the ceramic material is randomly distributed in the form of aggregation / deposition or dispersion between the three-dimensional interpenetrating polymer phase, which can expand the amorphous region of the polymer, increase the number of interfaces of the solid electrolyte, and promote the dissociation of the lithium salt.
[0051] Example 2 In this embodiment, a thermosetting PAN-based composite solid electrolyte membrane is provided which is produced by a production method including the following steps. (1) 35 g of polyacrylonitrile copolymer powder (manufactured by Jyuma Manufacturing, PAN: 30,000 to 250,000), 3 g of lithium perchlorate, 3 g of propylene carbonate, and 10 g of lithium titanium aluminum phosphate (D50 particle size: 150 nm) were premixed in a closed planetary mixer at a rotation speed of 1500 rpm for 20 min; (2) The premixed material is taken out and added into a single screw extruder for melt extrusion, the melt extrusion temperature is 220°C, and the thickness of the prototype thick film obtained by melt extrusion is 300 μm; (3) The prototype thick film is stretched in both directions and cooled to obtain a 25 μm-thick formed solid electrolyte thin film, i.e., a thermosetting PAN-based composite solid electrolyte film. The above operations must be performed in an environment with a humidity of not more than 5%.
[0052] The compaction density of the thermosetting PAN-based composite solid electrolyte membrane produced in this example is 3.8 g / cm 3 , the density of thermosetting PAN-based polymer fiber is 1.184g / cm 3 The diameter of the thermosetting PAN-based polymer fiber is 80 nm, and the number of thermosetting PAN-based polymer fibers per unit membrane area calculated by the above formula 1) is 1.6 × 10 6 The ionic conductivity of the thermosetting PAN-based composite solid electrolyte membrane is shown in FIG. 3b. The ionic conductivity calculated from the data shown in FIG. 3b is 6×10 -4 S / cm.
[0053] Example 3 In this embodiment, a thermosetting PAN-based composite solid electrolyte membrane is provided which is produced by a production method including the following steps. (1) 60 g of polyacrylonitrile copolymer powder (Jiema Manufacturing, PAN: 30,000 to 250,000), 6 g of lithium bis(fluorosulfonyl)imide, 6 g of dimethyl octadecyl hydroxy ethyl ammonium nitrate, and 20 g of lithium lanthanum zirconium tantalum oxygen fast ion conductor (D50 particle size: 150 nm) were premixed in a closed planetary mixer at a rotation speed of 2000 rpm for 15 min; (2) The premixed material is taken out and added into a single screw extruder for melt extrusion, the melt extrusion temperature is 200°C, and the thickness of the prototype thick film obtained by melt extrusion is 320 μm; (3) The prototype thick film is stretched in both directions and cooled to obtain a 33 μm-thick formed solid electrolyte thin film, i.e., a thermosetting PAN-based composite solid electrolyte film. The above operations must be performed in an environment with a humidity of not more than 5%.
[0054] The compaction density of the thermosetting PAN-based composite solid electrolyte membrane produced in this example is 4.1 g / cm 3 , the density of thermosetting PAN-based polymer fiber is 1.184g / cm 3 The diameter of the thermosetting PAN-based polymer fiber is 240 nm, and the number of fibers per unit membrane area calculated by the above formula 1) is 5.7 × 10 5 The ionic conductivity of the thermosetting PAN-based composite solid electrolyte membrane is shown in FIG. 3c. The ionic conductivity calculated from the data shown in FIG. 3c is 5×10 -4 S / cm.
[0055] Example 4 In this embodiment, a thermosetting PAN-based composite solid electrolyte membrane is provided which is produced by a production method including the following steps. (1) 60 g of polyacrylonitrile copolymer powder (manufactured by Jiema Manufacturing, PAN: 30,000 to 250,000), 15 g of lithium hexafluorophosphate, 12 g of succinonitrile, and 6 g of nanoalumina (D50 particle size: 170 nm) were premixed in a closed planetary mixer at a rotation speed of 2000 rpm for 10 min; (2) The premixed material is taken out and added into a single screw extruder for melt extrusion, the melt extrusion temperature is 180°C, and the thickness of the prototype thick film obtained by melt extrusion is 330 μm; (3) The prototype thick film is stretched in both directions and cooled to obtain a 35 μm-thick formed solid electrolyte thin film, i.e., a thermosetting PAN-based composite solid electrolyte film. The above operations must be performed in an environment with a humidity of not more than 5%.
[0056] The compaction density of the thermosetting PAN-based composite solid electrolyte membrane produced in this example is 3.1 g / cm 3, the density of thermosetting PAN-based polymer fiber is 1.184g / cm 3 The diameter of the thermosetting PAN-based polymer fiber is 200 nm, and the number of fibers per unit membrane area calculated by the above formula 1) is 5.2 × 10 5 The ionic conductivity of the thermosetting PAN-based composite solid electrolyte membrane is shown in FIG. 3D. The ionic conductivity calculated from the data shown in FIG. 3D is 2.3×10 -4 S / cm.
[0057] Example 5 In this embodiment, a thermosetting PAN-based composite solid electrolyte membrane is provided which is produced by a production method including the following steps. (1) 60 g of polyacrylonitrile copolymer powder (manufactured by Jiema Manufacturing, PAN: 30,000 to 250,000), 20 g of lithium difluoro(oxalato)borate, 15 g of succinonitrile, and 9 g of halide electrolyte Li3InCl6 (D50 particle size: 200 nm) were premixed in a closed planetary mixer at a rotation speed of 1500 rpm for 20 min; (2) The premixed material is taken out and added into a single screw extruder for melt extrusion, the melt extrusion temperature is 200°C, and the thickness of the prototype thick film obtained by melt extrusion is 280 μm; (3) The prototype thick film is stretched in both directions and cooled to obtain a 22 μm-thick formed solid electrolyte thin film, i.e., a thermosetting PAN-based composite solid electrolyte film. The above operations must be performed in an environment with a humidity of not more than 5%.
[0058] The compaction density of the thermosetting PAN-based composite solid electrolyte membrane produced in this example is 4.0 g / cm 3 , the density of thermosetting PAN-based polymer fiber is 1.184g / cm 3 The diameter of the thermosetting PAN-based polymer fiber is 100 nm, and the number of fibers per unit membrane area calculated by the above formula 1) is 1.4 × 10 6 / cm; the ionic conductivity of the thermosetting PAN-based composite solid electrolyte membrane is 8×10 -4 S / cm.
[0059] Comparative Example 4-1 In this comparative example, a thermosetting PAN-based composite solid electrolyte membrane was produced under the condition that no modifying auxiliary was added, and the production method specifically includes the following steps: (1) 60 g of polyacrylonitrile copolymer powder (Jiema Manufacturing, PAN: 30,000 to 250,000), 15 g of lithium hexafluorophosphate, and 6 g of nano-alumina (D50 particle size: 170 nm) were premixed in a closed planetary mixer at a rotation speed of 2000 rpm for 10 min; (2) The premixed material was taken out and added to a single screw extruder for melt extrusion. The melt extrusion temperature was set to 220°C, but extrusion film formation was not possible. Analysis of the cause revealed that the material was not melted at that temperature and therefore could not be extruded; when the melt extrusion temperature was gradually increased to above 240°C, extrusion was not possible, but the powder discolored and gas was released, indicating that dehydrogenation and thermal decomposition reactions occurred in the polyacrylonitrile copolymer under those temperature conditions.
[0060] As is clear from the comparison between Example 4 and Comparative Example 4-1, if the modification aid is not added when producing a thermosetting PAN-based composite solid electrolyte membrane, the melting point temperature of the polyacrylonitrile copolymer (still about the original 310°C) cannot be reduced. In this case, the polyacrylonitrile copolymer undergoes thermal decomposition first during the production process, and ultimately, a thermosetting PAN-based composite solid electrolyte membrane having high pressure density and high ionic conductivity cannot be produced by the melt drawing method.
[0061] Application Example 1 In this application example, a solid-state lithium ion battery is provided in which the thermosetting PAN-based composite solid electrolyte membrane provided in the embodiment 1 of the present invention is used as a solid electrolyte, and the assembly of the solid-state lithium ion battery specifically includes the following steps: 1) High nickel ternary positive electrode, i.e. Li(Ni 0.8 Mn 0.1 Co 0.1)O2 and NCM811 were used as the positive electrode materials, and the mass fractions of NCM811, carbon black conductive material (SP), and polyvinylidene fluoride (PVDF) (i.e., mass fractions calculated based on the total weight of NCM811, carbon black conductive material, and polyvinylidene fluoride) were mixed to be 97%, 1.3%, and 1.7%, respectively, and then the mixture was coated, roll pressed, pressed into pole pieces, and baked to produce a loading capacity of 44 mg / cm. 2 , fabricate NCM811 positive electrode pieces with a diameter of 12 mm; It is necessary to carry out the above step 1) in a dry environment with a humidity level not exceeding 5%; 2) The NCM811 positive electrode piece with a diameter of 12 mm prepared in the above step 1) is used as the positive electrode piece, and the thermosetting PAN-based composite solid electrolyte membrane provided in Example 1 is used as the intermediate film. No liquid is dripped, and finally, a general metallic lithium piece with a diameter of 14 mm is used as the negative electrode piece, which is covered and sealed, thus completing the assembly of the buckle battery.
[0062] The above step 2) is carried out in a glove box.
[0063] As a result of carrying out a charge-discharge cycle analysis on the solid-state lithium ion battery provided in this application example, the charge-discharge cycle graph of the solid-state lithium ion battery is as shown in FIG. 4. As can be seen from FIG. 4, the thermosetting PAN-based composite solid electrolyte film prepared in Example 1 is used as an intermediate film to assemble an all-solid-state buckle battery, and the battery can be stably cycled more than 300 times, which is an advanced level currently being researched. Therefore, the thermosetting PAN-based composite solid electrolyte film provided in the embodiment of the present invention can not only provide high ionic conductivity, but also effectively reduce interface impedance and ensure stable cycle of the all-solid-state battery.
[0064] The above is merely a specific embodiment of the present invention, and does not limit the scope of the present invention. Therefore, the replacement of equivalent parts, or the equivalent changes and modifications made according to the scope of protection of the present invention, are all within the scope of the present invention. In addition, the technical features of the present invention can be freely combined and used between technical features, between technical features and technical inventions, and between technical inventions and technical inventions.
Claims
1. A raw material composition for producing a thermosetting PAN-based interlayer film, The raw material composition includes a thermosetting PAN-based polymer material, a lithium salt, and a modifying aid, The mass ratio of the thermosetting PAN-based polymer material to the lithium salt is 20:1 to 3:1, and the mass ratio of the thermosetting PAN-based polymer material to the modifying assistant is 18:1 to 3:1; The raw material composition, characterized in that the modifying aid comprises one or a combination of several modified agents selected from a carbonate-based modifying aid, a nitrile-based modifying aid, and an ionic liquid-based modifying aid.
2. The raw material composition further includes a ceramic material, and the amount of the ceramic material used is 5 to 80 wt % when the total weight of the thermosetting PAN-based polymer material is 100%, Preferably, the amount of the ceramic material used is 10 to 50 wt %; More preferably, the ceramic material contains an inorganic ion conductor and / or an inorganic non-ion conductor, More preferably, the inorganic ion conductor comprises one or more selected from oxides, halides, sulfides, nitrides and carbides, and the inorganic non-ion conductor comprises one or more selected from metal oxides and non-metal oxides; More preferably, the ceramic material contains one or more oxides selected from a titanium-containing oxide, an aluminum-containing oxide, a boron-containing oxide, a zirconium-containing oxide, and a silicon-containing oxide; More preferably, the ceramic material comprises one or a combination of several selected from the group consisting of silica, alumina, lithium titanium aluminum phosphate, lithium borate, lithium borate ester, lithium zirconate, garnet-type lithium lanthanum zirconium oxygen, lithium indium chlorohalide, argyrogenite-type sulfide, lithium borohydride, and lithium lanthanum zirconium tantalum oxygen fast ion conductors.
3. The modifying aid is a carbonate-based modifying aid or a nitrile-based modifying aid, 2. The raw material composition according to claim 1, wherein the modifying aid is preferably a carbonate-based modifying aid.
4. The carbonate-based modifying aid includes one or more selected from ethylene carbonate, propylene carbonate, butene carbonate, and methyl ethyl carbonate, More preferably, the nitrile-based modification aid comprises one or more selected from butyronitrile, succinonitrile, valeronitrile, hexanitrile, hexanedinitrile, heptanitrile, octanenitrile, n-dodecanonitrile, n-tridecanonitrile, and n-tetradecanonitrile; More preferably, the cation in the ionic liquid-based modifying aid comprises one or more selected from the group consisting of alkyl quaternary ammonium cations, alkyl quaternary phosphonium cations, N,N-dialkylimidazole cations, and N-alkylpyridine cations, and the anion comprises one or more selected from the group consisting of halogen ions, acetate ions, nitrate ions, tetrafluoroborate ions, and trifluoroacetate ions.
5. The lithium salt includes one or more selected from the group consisting of lithium hexafluorophosphate, lithium perchlorate, lithium bisoxalate borate, lithium difluoro(oxalato)borate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide; The raw material composition according to any one of claims 1 to 3, characterized in that the thermosetting PAN-based polymer material is a copolymer of a monomer containing acrylonitrile or a derivative thereof, and itaconic acid or a derivative thereof.
6. The thermosetting PAN-based polymer material is a thermosetting PAN-based polymer fiber, and the number of the thermosetting PAN-based polymer fibers per unit membrane length is 1×10 3 ~1×10 7 / cm, and the diameter of the thermosetting PAN-based polymer fiber is 50 nm to 2 μm; The number of the thermosetting PAN-based polymer fibers per unit membrane length was calculated by the following formula 1), (Equation 1) N=4ρ' / (dρ) Equation 1) In the above formula 1), ρ' is the intermediate compaction density of the thermosetting PAN-based polymer fiber, and its unit is g / cm 3 ρ is the density of the thermosetting PAN-based polymer fiber, expressed in g / cm 3 6. The raw material composition according to claim 1, wherein d is an average diameter of the thermosetting PAN-based polymer fiber, and the unit is cm.
7. A manufacturing method for producing a thermosetting PAN-based interlayer film, comprising: The raw material composition is premixed and then melt-extruded, and the extruded prototype thick film is then stretched and / or thin-film molded to obtain the thermosetting PAN-based interlayer film; The raw material composition is the raw material composition according to any one of claims 1 to 6 for producing the thermosetting PAN-based interlayer film.
8. The process according to claim 7, characterized in that the temperature of the melt extrusion is 80-350°C, preferably 120-300°C.
9. The manufacturing method includes: Step (1): A step of premixing a raw material composition for producing the thermosetting PAN-based interlayer film to obtain a premixed material; Step (2): melt extruding the premixed material to obtain a prototype thick film; Step (3): performing a stretching process and / or a thin film forming process on the prototype thick film to obtain the thermosetting PAN-based intermediate film; or Step (1)': A step of premixing a thermosetting PAN-based polymer material and a modifying auxiliary in a raw material composition for producing the thermosetting PAN-based intermediate film to obtain a premixed material; Step (2)': performing melt extrusion on the premixed material to obtain a prototype thick film; Step (3)': performing a stretching process and / or a thin film forming process on the prototype thick film to obtain an intermediate film product; Step (4)': immersing the intermediate film product in a lithium salt solution or uniformly spraying the lithium salt solution on both sides of the intermediate film product, and then drying to obtain the thermosetting PAN-based intermediate film; Including, Preferably, in the step (2) and the step (2)', the apparatus used for the melt extrusion independently includes one or a combination of several selected from a ball mill, an internal mixer, a single screw extruder, a twin screw extruder, a multi-screw extruder, and a granulator; More preferably, in steps (2) and (2)', the thickness of the prototype thick film is independently between 100 μm and 2 mm; More preferably, in the step (3) and the step (3)', the stretching treatment independently includes transverse stretching, longitudinal stretching, or bidirectional stretching, More preferably, in the step (4)', the drying temperature is 70 to 90° C., More preferably, in step (4)', the solvent used for the lithium salt solution comprises isopropanol and / or dimethyl ether.
10. A thermosetting PAN-based interlayer film, produced by the method according to any one of claims 7 to 9.
11. The thermosetting PAN-based intermediate film is a liquid electrolyte separator or a solid electrolyte membrane, The thickness of the solid electrolyte membrane is preferably 1 to 100 μm, more preferably 5 to 60 μm, and even more preferably 15 to 30 μm. More preferably, the range of the compaction density of the solid electrolyte membrane is 0.8 to 4.5 g / cm 3 The thermosetting PAN-based interlayer film according to claim 10,
12. An electrochemical device comprising a liquid electrochemical device and a solid electrochemical device, the liquid electrochemical device including a separator, and the solid electrochemical device including a solid electrolyte membrane, 12. An electrochemical device, wherein the separator is the liquid electrolyte separator according to claim 11, and the solid electrolyte membrane is the solid electrolyte membrane according to claim 11.
Citation Information
Patent Citations
Composite solid electrolyte membrane and preparation method thereof
CN111740156A
solid polymer electrolyte
JP2003508886A
Solid electrolyte, its preparation method and application
JP2021514108A